THE DIFFICULTIES OF WRITING A RESEARCH PROPOSAL BY STUDENTS OF STIBA IEC JAKARTA - Valda Afiah; Suhendar Suhendar; Budiarto Budiarto (STIBA IEC JAKARTA, 2023)
This research aims to analyze the English Literature students’ of STIBA – IEC Jakarta problems in writing final project in English. The causes are viewed from students’ and the lecturers perspective as the advisor and also what are supposed to do to help the student minimize the problems in writing final project. This study used descriptive qualitative method that fully describe the problems as well as solutions in writing final projects. The deep analysis has been done from the student’s and the lecturer’s perspectives. After conducting a survey by doing some interviews and distributing questionnaires, we found that there are so many factors that affects the studnts’ difficulties in finishing their final projects. This research method is a method of classroom action research conducted to improve the ability of students to make a research proposal through a direct learning model. The process of implementation of the measures is implemented in stages until the research is successful. The procedure initiated actions of (1) the action plan, (2) implementation of the action, (3) observation, and (4) reflection. Results research shows that the ability to write a student thesis research proposal in semesters 7-8 English Literature Study Program 2018 academic year belongs to sufficient qualifications. Semester 7-8 students of the English Literature Study Program STIBA - IEC Jakarta should be helped to really understand how to prepare a thesis research proposal so that they can write research proposals well and in the end students will be able to complete the thesis quickly and on time.